Close identity of a pressure-stabilized intermediate with a kinetic intermediate in protein folding - Kitahara, Ryo (The National Academy of Sciences, 2003)
Atomic detailed structural study of a transiently existing folding intermediate is severely limited because of its short life. In ubiquitin, we found that a pressure-stabilized equilibrium conformer shares a common structural feature with the proline-trapped kinetic intermediate found in a pulse-labeling (1)H/(2)H exchange NMR study [Briggs, M. S. & Roder, H. (1992) Proc. Natl. Acad. Sci. USA 89, 2017–2021]. The conformer is locally unfolded in the entire segment from residues 33 to 42 and in C-terminal residues 70–76. The close structural identity of an equilibrium intermediate stabilized under pressure with a transiently observed folding intermediate is likely to be general in terms of a folding funnel common to both experiments.